2020
DOI: 10.1002/hipo.23290
|View full text |Cite
|
Sign up to set email alerts
|

Maximal aerobic capacity is associated with hippocampal cognitive reserve in older adults with amnestic mild cognitive impairment

Abstract: Maximal aerobic capacity (MAC) has been associated with preserved neural tissue or brain maintenance (BM) in healthy older adults, including the hippocampus. Amnestic mild cognitive impairment (aMCI) is considered a prodromal stage of Alzheimer's disease. While aMCI is characterized by hippocampal deterioration, the MAC‐hippocampal relationship in these patients is not well understood. In contrast to healthy individuals, neurocognitive protective effects in neurodegenerative populations have been associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…Mormino et al (2012) found successful episodic memory encoding to be associated with right hippocampal hyperactivity in cognitively normal older adults with high Aβ burden compared with young adults and older adults without significant AD pathology. While not reporting on the specific relationship between the hippocampal hyperactivity and post-task memory performance, they demonstrated that the general increase in brain activity observed in the high-risk participants was associated with favorable memory performance, suggesting for a compensatory mechanism as being previously shown in patients with amnestic MCI (Dickerson et al, 2005;Eisenstein et al, 2020). However, this explanation was ruled out in the current cognitively intact sample, since the increased hippocampal activity was not associated with better memory performance in each group separately or at the whole sample level.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mormino et al (2012) found successful episodic memory encoding to be associated with right hippocampal hyperactivity in cognitively normal older adults with high Aβ burden compared with young adults and older adults without significant AD pathology. While not reporting on the specific relationship between the hippocampal hyperactivity and post-task memory performance, they demonstrated that the general increase in brain activity observed in the high-risk participants was associated with favorable memory performance, suggesting for a compensatory mechanism as being previously shown in patients with amnestic MCI (Dickerson et al, 2005;Eisenstein et al, 2020). However, this explanation was ruled out in the current cognitively intact sample, since the increased hippocampal activity was not associated with better memory performance in each group separately or at the whole sample level.…”
Section: Discussionmentioning
confidence: 91%
“…While increased hippocampal activity or hyperactivity has been generally demonstrated to be associated with poorer neurobiological and cognitive outcomes in cognitively healthy older adults, it has been both negatively and positively linked with cognitive and clinical outcomes in patients with MCI (Kircher et al, 2007;Clement and Belleville, 2010;Bakker et al, 2012;Huijbers et al, 2015;Eisenstein et al, 2020). For example, increased left hippocampal activation during memory encoding in MCI was correlated with better memory performance and cognitive-clinical status in some studies (Kircher et al, 2007;Clement and Belleville, 2010), while others found it to be associated with poorer memory performance and increased Aβ burden (Bakker et al, 2012;Huijbers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mormino et al 9 found successful episodic memory encoding to be associated with right hippocampal hyperactivity in cognitively normal older adults with high Aβ burden compared to young adults and older adults without significant AD pathology. While not reporting on the specific relationship between the hippocampal hyperactivity and post-task memory performance, they demonstrated that the general increase in brain activity observed in the high-risk participants was associated with favourable memory performance, suggesting for a compensatory mechanism as being previously shown in patients with amnestic mild cognitive impairment 13,58 . This explanation was ruled out in the cognitively healthy sample of the current study since while the active group which demonstrated lower hippocampal activity also showed higher memory performance, increased hippocampal activity was also not associated with better memory performance in each group separately or at the whole sample level.…”
Section: Discussionmentioning
confidence: 81%
“…While increased hippocampal activity or hyperactivity has been generally demonstrated to be associated with poorer neurobiological and cognitive outcomes in cognitively healthy older adults, it has been both negatively and positively linked with cognitive and clinical outcomes in patients with MCI [11][12][13][14][15] . For example, increased left hippocampal activation during memory encoding in MCI was correlated with better memory performance and cognitive-clinical status in some studies 11,12 , while others found it to be associated with poorer memory performance and increased Aβ burden 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation